Enhancing Elementary Science Learning through Android-Based Interactive Media with Construct 2 - Hendra Nelva Saputra; Darman Darman; Nurnaningsih Nurnaningsih (Universitas Pendidikan Ganesha, 2025)
Low student understanding of food web concepts in science subjects remains a challenge due to conventional teaching methods and minimal use of interactive media. This study aims to develop and test the effectiveness of Android based interactive learning media designed using Construct 2 to enhance fifth grade students’ conceptual understanding in science. This research is a development study (research and development) using the ADDIE model through the stages of Analyze, Design, Development, Implementation, and Evaluation. The research subjects consisted of media experts, subject matter experts, and students. Data were collected through expert validation questionnaires, student response questionnaires, and learning outcome tests, and then analyzed using the One Sample t-test. Validation results indicated that the media was highly feasible for use, with average scores of 85% from media experts and 93.33% from subject matter experts, while student responses reached 83.75%. The t-test results showed an average student score of 73.13, which was significantly higher than the reference score of 68 (p = 0.004). In conclusion, Android-based interactive learning media developed using Construct 2 was proven effective in improving students’ understanding and learning outcomes. Its implication is that this media can serve as an innovative learning strategy that enhances students’ motivation, engagement, and understanding, while also providing a model for adaptive and contextual digital media development in modern education.